Lessons Learned from Developing an Industry 4.0 Mobile Process Management System Supported by Artificial Intelligence - Kalinowski, Mateusz; Weichbroth, Paweł (Wnioski z rozwoju mobilnego systemu zarządzania procesami Przemysłu 4.0 wspieranego sztuczną inteligencją, 2022)
Research, development and innovation (RDI) projects are undertaken in order to improve existing, or develop new, more efficient products and services. Moreover, the goal of innovation is to produce new knowledge through research, and disseminating it through education and training. In this line of thinking, this paper reports and discusses the lessons learned from the undertaken project, regarding three areas: machine learning (artificial intelligence), computational intelligence, and database management systems (DBMS). As nowadays, a numerous of the RDI projects are oriented towards the development of dataintensive solutions, the authors are confident that these lessons will be valuable not only for data engineers, but also for those researchers and practitioners who are dealing with the issues related to building and validating machine learning models, applications of moving averages to high-frequency data streams, and the implementation and deployment of DBMS.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 1 (63), s. 9-19
Keywords: Industry 4.0; mobile; process management; artificial intelligence; research; development and innovation; przemysł 4.0; mobilność; zarządzanie procesami; sztuczna inteligencja